INSEAD Jan18 Admission Decisions - Join Us in the Chat for Live Decision Updates

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

1) -M = |-M| only when M = 0 --> Suff 2) M = 3 or -3 --> Insuff

For statment 1, It's not only M=0 that works. We could try any negative number.
We can pick one example:
o If M = -10, then -M=-(-10) = 10 and |-M| = |-(-10)| = |10| = 10...

1) -M = |-M| only when M = 0 --> Suff 2) M = 3 or -3 --> Insuff

For statment 1, It's not only M=0 that works. We could try any negative number. We can pick one example: o If M = -10, then -M=-(-10) = 10 and |-M| = |-(-10)| = |10| = 10...

So statment 1 alone is not enough

Can someone explain how M can be negative in Statement 1?

1) -M = |-M| only when M = 0 --> Suff 2) M = 3 or -3 --> Insuff

For statment 1, It's not only M=0 that works. We could try any negative number. We can pick one example: o If M = -10, then -M=-(-10) = 10 and |-M| = |-(-10)| = |10| = 10...

So statment 1 alone is not enough

Can someone explain how M can be negative in Statement 1?

I can try

As we have abs ( something ) >= 0, we have:
|-M| >= 0
<=> -M >= 0 as |-M| = -M
<=> M =< 0

1) -M = |-M| only when M = 0 --> Suff 2) M = 3 or -3 --> Insuff

For statment 1, It's not only M=0 that works. We could try any negative number. We can pick one example: o If M = -10, then -M=-(-10) = 10 and |-M| = |-(-10)| = |10| = 10...

So statment 1 alone is not enough

Can someone explain how M can be negative in Statement 1?

I can try

As we have abs ( something ) >= 0, we have: |-M| >= 0 <M>= 0 as |-M| = -M <=> M =< 0

Sorry I am being slow - what I am getting for 1 is -M = |-M| so M = |M| and |M| is never negative... so on that basis I concluded that M has to be positive ... I'm not sure where I have gone wrong?

1) -M = |-M| only when M = 0 --> Suff 2) M = 3 or -3 --> Insuff

For statment 1, It's not only M=0 that works. We could try any negative number. We can pick one example: o If M = -10, then -M=-(-10) = 10 and |-M| = |-(-10)| = |10| = 10...

So statment 1 alone is not enough

Can someone explain how M can be negative in Statement 1?

I can try

As we have abs ( something ) >= 0, we have: |-M| >= 0 <M>= 0 as |-M| = -M <=> M =< 0

Sorry I am being slow - what I am getting for 1 is -M = |-M| so M = |M| and |M| is never negative... so on that basis I concluded that M has to be positive ... I'm not sure where I have gone wrong?

Sorry I am being slow - what I am getting for 1 is -M = |-M| so M = |M| and |M| is never negative... so on that basis I concluded that M has to be positive ... I'm not sure where I have gone wrong?

In bold, it's not correct

We have |M| = |-M|.... but we do not have -M = M

Thanks - so where is the error in my statement below:

Lets take say - M=-3/3 In that case, the Abs is |3|. If -M=|-M| -M=|-3|

If that's the case doesnt -M=-3? or does it equal 3 / -3

Im really lost as to what the rule is here... any chance you could explain in words (in order to help a rather math challeneged lawyer understand the concepts at play?)

Sorry I am being slow - what I am getting for 1 is -M = |-M| so M = |M| and |M| is never negative... so on that basis I concluded that M has to be positive ... I'm not sure where I have gone wrong?

In bold, it's not correct

We have |M| = |-M|.... but we do not have -M = M

Thanks - so where is the error in my statement below:

Lets take say - M=-3/3 In that case, the Abs is |3|. If -M=|-M| -M=|-3|

If that's the case doesnt -M=-3? or does it equal 3 / -3

Im really lost as to what the rule is here... any chance you could explain in words (in order to help a rather math challeneged lawyer understand the concepts at play?)

THANKS!

I will try ... I'm perhaps less expert in pure word explanations

I think u have a mixture in your reasoning between inferences from abs properties and lines of calculation.

First of all, -M = -3 cannot be chosen because M must be negative ... But, I can take this value and demonstrate that it's not working

So, in your example, -M = -3 implies that M = 3. We will consider seperatly the left side of the original equation and then the right one. The objective is to find the same value, indicating that both sides are equal one another.

Sides:
o At left, -M = -3.
o At right, |-M| = |-3| = 3

To conclude on your example, -3 is not equal to 3 implies that M cannot be 3 or -M cannot be -3 and at the same satisfies the equation -M = |-M|

Now, back to the original equation. Luckily, we have 1 property of abs that is very useful : abs (something) >= 0.

By using the original equation, we know now that -M must be positive or equal to 0 to make M a solution to -M = |-M|. M is, by this way, negative or 0.

Another way to see it is to set Z = -M. That means Z = |Z| implies Z positive or 0. Thus, M, the opposite of Z on a number line, is negative or 0.

I will try ... I'm perhaps less expert in pure word explanations

I think u have a mixture in your reasoning between inferences from abs properties and lines of calculation.

First of all, -M = -3 cannot be chosen because M must be negative ... But, I can take this value and demonstrate that it's not working

So, in your example, -M = -3 implies that M = 3. We will consider seperatly the left side of the original equation and then the right one. The objective is to find the same value, indicating that both sides are equal one another.

Sides: o At left, -M = -3. o At right, |-M| = |-3| = 3

To conclude on your example, -3 is not equal to 3 implies that M cannot be 3 or -M cannot be -3 and at the same satisfies the equation -M = |-M|

Now, back to the original equation. Luckily, we have 1 property of abs that is very useful : abs (something) >= 0.

By using the original equation, we know now that -M must be positive or equal to 0 to make M a solution to -M = |-M|. M is, by this way, negative or 0.

Another way to see it is to set Z = -M. That means Z = |Z| implies Z positive or 0. Thus, M, the opposite of Z on a number line, is negative or 0.